Australian senior adventure travellers to Peru: Maximising older tourists' travel health experience - Bauer, Irmgard (Elsevier Science, 2012)
Summary Financially comfortable, with ample spare time and much better health, olderpeople travel more than ever and to more adventurous destinations. Taking Australian senioradventure travellers to Peru as an example, travel health preparations need to take intoaccount the phenomenon ‘senior traveller’, the destination with its attractions and challenges,and age-related changes and restrictions. The need for routine travel health advice,vaccinations and prophylaxis remains unchanged. However, more emphasis should be placedon locality-specific issues so that age-appropriate advice and preparations maximize thechances for a safe and memorable travel experience.